Do Cyborgs Desire Their Own Subjection? Thinking Anthropology With Cinematic Science Fiction. (February 2016) - Dickson, Jessica
Primarily a thought experiment, this essay explores how cinematic cyborgs and anthropological approaches to personhood and subjectivity might be theorized together. The 1980s and 1990s showed considerable investment by media producers, and strong reception by audiences and culture critics, to science fiction (SF) film and television franchises that brought new attention to the imagined cyborg subject in the popular imagination of the time. Outside of Hollywood, this same period was marked by biomedical and technological advancements that raised profound implications for Western conceptions of personhood. While SF has enjoyed a long-standing position in the social sciences, primarily with sociologists and feminist theorists, SF's preoccupation with what it means to be human calls for anthropological engagement as well. Yet if Donna Haraway envisioned cyborgs as celebrated sites of gender de/reconstruction and open possibility, why is it that cinematic cyborgs desire so strongly to become subjects of mothers, lovers, government, and God? While primary attention is given here to film texts and academic articles that drove discussions of science and technology in popular culture during the decades preceding the millennium, with remakes, reboots, and sequels to popular franchises underway, a renewed interest in the anthropological questions these films and series provoke is evident.